Kebersihan Makam Berbasis Gotong Royong sebagai Upaya Peningkatan Kepedulian Lingkungan di Desa Talang Dantuk - Dhania Nabila; Denti Narti; Deni Efrianti; Iin Karnila; Nabilla Afifa Amatullah; Devina Ninosari; Tita Septi Handayani; Martha Heriniazwi Dianthi (Jurnal Dehasen Mengabdi, 2026)
Environmental cleanliness is an important aspect in maintaining comfort, health, and social values within the community, including cemetery areas. Village cemeteries serve not only as burial sites but also hold religious and social significance that must be preserved. Talang Dantuk Village, Seluma District, Seluma Regency, faces challenges related to inadequate maintenance and cleanliness of cemetery areas due to limited time, facilities, and community awareness. This community service activity aims to enhance public awareness and participation in maintaining cemetery cleanliness through collective cleaning activities based on mutual cooperation. The methods included initial observation, coordination with village authorities and community leaders, implementation of joint cemetery cleaning activities, and evaluation and follow-up. The results indicate increased community awareness, improved cleanliness and organization of the cemetery area, and strengthened community solidarity. This activity is expected to serve as an initial step toward sustainable maintenance of village cemetery cleanliness.